Styles of coping with stress and locus of control in sporting situations in a group of young female football players - Rutkowska, K.; Bergier, J.; Witkowski, Z. (Human Movement, 2014)
The objective of the present study to analyse the styles of coping with stress and the locus of control (LOC) in specific sporting situations of female football players and seeking relationships between the analysed variables. Methods. The study included 50 female football players aged 16-18 years. Two psychological instruments were administered: the Polish language Questionnaire for Examining Locus of Control in Sports Activity (PKSPwS) and the Polish version of the Coping Inventory for Stressful Situations (CISS). Results. The mean level of the investigated LOC dimensions as well as the styles of coping with stress showed that behaviour associated with avoidance and emotions predominated over task-oriented style. However, taskoriented style was positively related to the locus of control in specific situations that occur in sport. Conclusions. The results of the study suggest that social support and educational initiatives adapted to female athletes are required. These include mental training and the psycho-pedagogical intervention of coaches, where emphasis should be placed on enhancing internal locus of control as well as the development and improvement of effective stress-coping styles.